FAKTOR-FAKTOR PELAYANAN KESEHATAN YANG MEMPENGARUHI KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH DR. H. CHASAN BOESOIRIE TERNATE - M. Idham Masuku; Lutfan Lazuardi; Mubasysyir Hasanbasri (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Complaint is important response from a patient who has a unique information and valuable for the organization to improve quality of service and risk management. The challenge for the hospital organization now is how to catch and using information from the patients productive to improve the quality, safety, and it gives the accessibility to care patient system or medication. Hospital DR. H. Chasan Boesoirie Ternate in 2014 began to hold a counter services for complaints and information from the public. Based on the data, throughout the year 2014 there were four reports of complaints from external customers and internal one complaints from customers. Objective: Knowing the health service factors that affect the satisfaction of outpatients in RSUD DR. H. Chasan Boesoirie Ternate. Methods: This research qualitative eksploratif by using the draft case study. Subjects is the patients out as much as 16 respondents. Results: Existed dissatisfaction patients such as silent, anger and rage, protest, complaint and compare to the hospital, and choose treated in a hospital. Factors that cause dissatisfaction with staff that is communication rude, make it harder for patients, and not discipline time. On the part of management, the waiting time and schedule information are uncertain. On the part environment, facilities and infrastructure, as well as medical equipment is not adequate. Conclusion: There is a dissatisfaction as evidence of dissatisfaction patients. Many factors that influence so that there dissatisfaction patients to service that it receives. Three components in service system in the hospital staff, management and environmental influenced by and each one another. It is advisable to see this as positive inputs in order to carry out quality improvement. The meeting the needs, and expectations a desire and it will be making customer satisfaction patients.